PENGEMBANGAN METODE ANALISIS SPEKTROFOTOMETRY UNTUK PENENTUAN KOLESTEROL DI DALAM MAKANAN TRADISIONAL - Situmorang, Manihar; Silitonga, P Maulim; Nurwahyuni, Isnaini; Siregar, Linda Sari (JURNAL PENELITIAN SAINTIKA, 2012)
The development of analytical UV-Vis spectrophotometric method forthe determination of cholesterol is explained. The assay performed by enzymaticcatalytic reaction Â·using cholesterol oxidase (COx) to . oxidise cholesterol into cholestenon and hydrogen peroxide followed by catalytic reduction of hydrogenperoxide with o-dianicidine by using enzyme peroxidase (POx) to produce red colour reduced o-dianicideine that can be measured at ii. 520 nm. The modifiedmethod gave sensitive response to cholesterol, where the detection linearity to cholesterol lies between 0.01-5.0 mM cholesterol, slope 0.158 aulmM cholesterol,and the detection limit of 0~01 mM cholesterol. The method has been applied for thedetermination of cholesterol in traditional food samples, where the concentrations ofcholesterol in food are lies between 0.052-0.799 mM cholestero)